Entrenamiento de la flexibilidad en voleibol sentado (2019)
The present investigation is a quasi-experimental study that shows the effects of a training program of the flexibility of the posterior chain on the functional reach and execution of the forearm pass in a group of sitting volleyball players from the Bogota league. This program was based on the combination of two techniques of flexibility development: proprioceptive neuromuscular facilitation (PNF) and dynamic stretching. It lasted six weeks, 17 sessions, each session of 30 minutes and two sessions for applying the pretest and posttest. The study shows statistical significance in the results of the flexibility test; however the significance in the results of the functional reach test or in the evaluation of the forearm pass is not obtained, although changes at clinical level are observed. There is also a correlation of statis-tical significance between the sit and reach test and the trunk inclination angle, measured through gesture analysis using Kinovea® software.